Developing Myanmar's Information and Communication Technology Sector toward Inclusive Growth - Kee-Yung Nam; Maria Rowena Cham; Paulo Rodelio Halili (Asian Development Bank (ADB), 2015)
Myanmar's recent socioeconomic and political reforms have signaled a readiness to reintegrate into the world economy. To leapfrog the economy and accelerate growth, the country should take advantage of digital technology. This paper assesses Myanmar's information and communication technology sector, identifies constraints the sector faces, and recommends policies that will help the government overcome them. Given limited public resources, Myanmar will need help translating its information and communication technology infrastructure needs into financially viable and bankable projects that can attract private sector financing.
hdl:11540/5254
Keywords: L86; L88; L96; L98; 330; e-governance; ICT infrastructure; information and communication technology development; Myanmar; telecommunications